High-resolution glycosylation site-engineering method identifies MICA epitope critical for shedding inhibition activity of anti-MICA antibodies. Issue 1 (2nd January 2019) - Lombana, T. Noelle; Matsumoto, Marissa L.; Berkley, Amy M.; Toy, Evangeline; Cook, Ryan; Gan, Yutian; Du, Changchun; Schnier, Paul; Sandoval, Wendy; Ye, Zhengmao; Schartner, Jill M.; Kim, Jeong; et al.
ABSTRACT: As an immune evasion strategy, MICA and MICB, the major histocompatibility complex class I homologs, are proteolytically cleaved from the surface of cancer cells leading to impairment of CD8 + T cell- and natural killer cell-mediated immune responses. Antibodies that inhibit MICA/B shedding from tumors have therapeutic potential, but the optimal epitopes are unknown. Therefore, we developed a high-resolution, high-throughput glycosylation-engineered epitope mapping (GEM) method, which utilizes site-specific insertion of N-linked glycans onto the antigen surface to mask local regions. We apply GEM to the discovery of epitopes important for shedding inhibition of MICA/B and validate the epitopes at the residue level by alanine scanning and X-ray crystallography (Protein Data Bank accession numbers 6DDM (1D5 Fab-MICA*008), 6DDR (13A9 Fab-MICA*008), 6DDV (6E1 Fab-MICA*008). Furthermore, we show that potent inhibition of MICA shedding can be achieved by antibodies that bind GEM epitopes adjacent to previously reported cleavage sites, and that these anti-MICA/B antibodies can prevent tumor growth in vivo .